X-ray studies bridge the molecular and macro length scales during the emergence of CoO assemblies - Grote, Lukas; Zito, Cecilia A. [UNESP]; Frank, Kilian; Dippel, Ann-Christin; Reisbeck, Patrick; Pitala, Krzysztof; Kvashnina, Kristina O.; Bauters, Stephen; Detlefs, Blanka; Ivashko, Oleh; Pandit, Pallavi; Rebber, Matthias; et al. (Springer Nature, 2021)
The key to fabricating complex, hierarchical materials is the control of chemical reactions at various length scales. To this end, the classical model of nucleation and growth fails to provide sufficient information. Here, we illustrate how modern X-ray spectroscopic and scattering in situ studies bridge the molecular- and macro- length scales for assemblies of polyhedrally shaped CoO nanocrystals. Utilizing high energy-resolution fluorescence-detected X-ray absorption spectroscopy, we directly access the molecular level of the nanomaterial synthesis. We reveal that initially Co(acac)3 rapidly reduces to square-planar Co(acac)2 and coordinates to two solvent molecules. Combining atomic pair distribution functions and small-angle X-ray scattering we observe that, unlike a classical nucleation and growth mechanism, nuclei as small as 2 nm assemble into superstructures of 20 nm. The individual nanoparticles and assemblies continue growing at a similar pace. The final spherical assemblies are smaller than 100 nm, while the nanoparticles reach a size of 6 nm and adopt various polyhedral, edgy shapes. Our work thus provides a comprehensive perspective on the emergence of nano-assemblies in solution.